2016
DOI: 10.3934/math.2017.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on an elliptic problem arising in weighted energy estimates for wave equations with space-dependent damping term in an exterior domain

Abstract: Abstract. This paper is concerned with weighted energy estimates and diffusion phenomena for the initial-boundary problem of the wave equation with space-dependent damping term in an exterior domain. In this analysis, an elliptic problem was introduced by Todorova and Yordanov. This attempt was quite useful when the coefficient of the damping term is radially symmetric. In this paper, by modifying their elliptic problem, we establish weighted energy estimates and diffusion phenomena even when the coefficient o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…As in [28] (see also [23] and [24]), we have By (5.4), we have J 1 ≤ K 1 (1 + t) − γ−α 2(2−α) (E 0 + E 1 ) 1 2 . By a computation similar to the one for J 1 , we deduce from (5.3) that…”
Section: Diffusion Phenomenamentioning
confidence: 81%
See 2 more Smart Citations
“…As in [28] (see also [23] and [24]), we have By (5.4), we have J 1 ≤ K 1 (1 + t) − γ−α 2(2−α) (E 0 + E 1 ) 1 2 . By a computation similar to the one for J 1 , we deduce from (5.3) that…”
Section: Diffusion Phenomenamentioning
confidence: 81%
“…Then in [23,24] the problem (1.1) in an exterior domain with non-radially symmetric damping terms satisfying lim |x|→∞ |x| α a(x) = a 0 > 0 could be considered and it is shown that the asymptotic behavior of solutions to (1.1) can be also given by the solution of (2.1), however, only when the initial data are compactly supported. We would summarize that if the initial data are not compactly supported, then a kind of weighted energy estimates is quite few; note that Ikehata gave one of weighted energy estimates in [8] but the initial data are required to have an exponential decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1.2 is proved in Section 2 by weighted energy method with a weight function having the form e ψ(t,x) with an appropriate function ψ(t, x) (see Definition 2.1). Such a weight function was developed by [21,60,48,56]. Making use of this weight, we can estimate the weighted energy of the solution by the sum of the initial energy and the nonlinear terms (see Lemma 2.4).…”
Section: Conjecturementioning
confidence: 99%
“…The space-dependent damping α ∈ R, β = 0 was also studied by [53,42,21,60,25,65,55,56,57,58], and similarly to the above, the behavior of the solution was classified in the following way: (i) Scattering: if α > 1, then the solution behaves like that of the wave equation without damping; (ii) Scale-invariant weak damping: if α = 1, then the asymptotic behavior of the solution depends on a 0 ; (iii) Effective: if α < 1, then the solution behaves like that of the corresponding parabolic equation. We note that in the space-dependent case, the overdamping phenomenon does not occur.…”
Section: Introductionmentioning
confidence: 99%